PERKEMBANGAN KOTA TUA PEJAT TAHUN 1999-2009 - -, Adol - (Pendidikan Sejarah, 2013)
The research explains about Developing of Tua Pejat City Year 1999-2009.Formulation of the research are: 1) How is condition of Tua Pejat while join with Kabupaten Padang Pariaman. 2) How develop Tua Pejat since 1999-2009 that is seen from phisyc, social , culture and economic aspects. The purpose of the research is to describe developing Tua Pejat year 1999-2009. the research uses history method with four steps like, 1) Heuristic is searching data and collecting sources such as primer sources is interview, meanwhile secunder sources is history books. 2) Source critique is analying data toward extern and intern. 3) interpretation is explaining data that is got from field with relate one fact and other fact appropriate history events. 4) Historiography is writing steps of history untill the research. The result of research show that Tua Pejat has bring changing after becoming Kabupaten because there are potential and city otonom, so Tua Pejat as a village change developing more better and good every part and will come many advantages for society. From the result of research, the reseacher can conclude alike, firstly, develop of Kota Tua Pejat year 1999-2009 bring for changing and developing every part because goverment has started condition of society. Secondly, building problem supermarket, roadway, market, healthy, transportation and education. Thirdly, city condition of Tua Pejat with city potencial by Kabupaten Kepulauan Mentawai.